Branched-chain amino acids are the primary limiting amino acids in the diets of endurance-trained men after a bout of prolonged exercise - Kato, H.; Suzuki, K.; Bannai, M.; Moore, D. R. (The Journal of Nutrition, 2018)
Background: The indicator amino acid oxidation (IAAO) method estimates the protein intake required to maximize whole-body protein synthesis and identify the daily protein requirement in a variety of populations. However, it is unclear whether the greater requirements for endurance athletes previously determined by the IAAO reflect an increased demand for all or only some amino acids. Objective: The aim of this study was to determine the primary rate-limiting amino acids in endurance-trained athletes after prolonged exercise, by measuring the oxidation of ingested [1-13C]phenylalanine in response to variable amino acid intake. Methods: Five endurance-trained men (means ± SDs: age, 26 ± 7 y; body weight, 66.9 ± 9.5 kg; maximal oxygen consumption, 63.3 ± 4.3 mL x kg-1 x min-1) performed 5 trials that involved 2 d of controlled diet (1.4 g protein x kg-1 x d-1) and running (10 km on day 1 and 5 km on day 2) prior to performing an acute bout of endurance exercise (20-km treadmill run) on day 3. During recovery on day 3, participants consumed test diets as 8 isocaloric hourly meals providing sufficient energy and carbohydrate but a variable amino acid intake. The test diets, consumed in random order, were deficient (BASE: 0.8 g x kg-1 ? d-1) and sufficient (SUF; 1.75 g x kg-1 ? d-1) amino acid diets modeled after egg protein, and BASE supplemented with branched-chain amino acids (BCAA diet; 1.03 g ? kg-1 x d-1), essential amino acids (EAA diet; 1.23 g x kg-1 x d-1), or nonessential amino acids (NEAA diet; 1.75 g x kg-1 x d-1). Whole-body phenylalanine flux (Q), 13CO2 excretion (F13CO2), and phenylalanine oxidation (OX) were determined according to standard IAAO methodology. Results: There was no effect of amino acid intake on Q (P = 0.43). F13CO2 was significantly (all P < 0.01) lower than BASE for the BCAA (~32%), EAA (~31%), and SUF (~36%) diet treatments. F13CO2 for the NEAA diet was ~18% lower than for BASE (P < 0.05) but ~28% greater than for SUF (P < 0.05). OX was similarly decreased (~24-41%) in all conditions compared with BASE (all P < 0.05). Conclusion: Our results suggest that the BCAAs may be the primary rate-liming amino acids in the greater daily protein requirement of endurance trained men